Intermittent streamflow generation in a merokarst headwater catchment. Issue 1 (23rd November 2022) - Hatley, Camden M.; Armijo, Brooklyn; Andrews, Katherine; Anhold, Christa; Nippert, Jesse B.; Kirk, Matthew F.
Abstract : Intermittent headwater streams are highly vulnerable to environmental disturbances, but effective management of these water resources requires first understanding the mechanisms that generate streamflow. Abstract : Intermittent headwater streams are highly vulnerable to environmental disturbances, but effective management of these water resources requires first understanding the mechanisms that generate streamflow. This study examined mechanisms governing streamflow generation in merokarst terrains, a type of carbonate terrain that covers much of the central United States yet has received relatively little attention in hydrological studies. We used high-frequency sampling of precipitation, stream water, and groundwater during summer 2021 to quantify the contributions to streamflow from different water sources and characterize their short-term dynamics in a 1.2 km 2 merokarst catchment at the Konza Prairie Biological Station (Kansas, USA). Mixing calculations using stable water isotopes and dissolved ions indicate that streamflow is overwhelmingly contributed by groundwater discharge from thin (1–2 m) limestone aquifers, even during wet periods, when soil water and surface runoff are generally expected to be more important. Relationships between hydraulic heads in the aquifers and their contributions to streamflow differed early in the study period compared to later, after a major storm occurred, suggesting there is a critical threshold of groundwater storage that the bedrock needs to attain before fully connecting to the stream. Furthermore, contributions from each limestone unit varied during the study period in response to differences in their hydrogeological properties and/or their stratigraphic position, which in turn impacted both the length of streamflow and its composition. Taken together, we interpret that the subsurface storage threshold and variation in aquifer properties are major controllers of flow intermittency in merokarst headwater catchments.